Bibliometric Analysis of Multy Representation (DMR) Discourse Learning Model on Mathematical Problem Solving in Elementary Schools - Firzi Sekarayu, Prisya; Amriyah, Chairul; Erfayliana, Yudesta (Indo-MathEdu Intellectuals Journal, 2025)
Research on the Multi-Representation Discourse (DMR) Learning Model in mathematics learning in elementary schools is still limited, especially related to developmental trends and their impact on mathematical problem solving. This study aims to map the research trend of the Multi-Representation Discourse (DMR) Learning Model in solving mathematics problems in elementary schools as well as thematic evolution and technology integration in DMR research. This study uses a bibliometric approach with publication analysis from Google Scholar (2015-2025) using Publish or Perish software and VOSviewer for overlay, density, and network visualization. The results of the analysis show the rapid development of DMR research in mathematics problem solving in elementary schools, with a focus on verbal communication, learning models, and teaching effectiveness. There is a shift towards the integration of technologies such as artificial intelligence and speech recognition, with five main thematic clusters: communication, model effectiveness, basic education, mathematical representation, and technology integration. This research provides insights into the development trends of DMR learning in primary education, which includes the use of technology to improve learning effectiveness.